Formation of school managers: Theoretical-practical contributions of historical-cultural psychology - Bulhões, Larissa Figueiredo Salmen Seixlack; Asbahr, Flávia da Silva Ferreira [UNESP] (Universidade Estadual de Maringa, 2017)
This work reports the experience of training school managers based on the theoretical assumptions of historical-cultural psychology. The intervention took place as one of the actions of the Project Education Without Borders (PESF) - a partnership between the Municipal Secretary of Education and the psychology department of a state University of São Paulo in assisting schools that have low IDEB (Basic Education Development Index). Study meetings were held monthly with the managers of the six participating schools and with representatives of the pedagogical department of the Municipal Secretary of Education. The themes of the meetings were established based on the demand of the group, which chose as study goals: 1. understanding the production of motives and interests for the students' learning and 2. understanding how the study activity is formed and developed as a main activity at school age. As a strategy of theoretical-practical articulation, the proposition of study tasks on the themes discussed in each meeting was adopted. As a reference, the concept of study task of Davydov and Markova (1987) was used. The results point out that the application of the theoretical assumptions of historical-cultural psychology to the concrete demands of the organization of teaching in the daily school life makes it possible to overcome the traditional dichotomy between theory and practice in teacher education and promotes the construction of new guidelines for pedagogical practice.
Keywords: Educational activity; School psychology; Teacher education